2017
DOI: 10.1071/ch17227
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of an Indinavir Precursor from Biomass-Derived (–)-Levoglucosenone

Abstract: Lignocellulosic biomass pyrolysis with acid catalysis selectively produces the useful chiral synthon 6,8-dioxabicyclo[3.2.1]oct-2-ene-4-one ((–)-levoglucosenone, LGO). In this report, LGO was used to prepare (3R,5S)-3-benzyl-5-(hydroxymethyl)-4,5-dihydrofuran-2(3H)-one, which is an intermediate used in the construction of antivirals including the protease inhibitor indinavir. To achieve the synthesis, the hydrogenated derivative of LGO was functionalised using aldol chemistry and various aromatic aldehydes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Burseran and Isostegane) while 2H‐HBO is an intermediate to C 7–12 5‐alk(en)yl‐γ‐lactones, which is known as Laiscent TM , a dairy flavor. LGO is a promising precursor for pharmaceuticals, with many applications having been reported in the 1980s–1990s, and with more recent examples being synthetic routes to the antiviral indinavir and a range of pharmaceutically active cyclopropylesters …”
Section: Products From C6 (Lgo and Hmf)mentioning
confidence: 99%
“…Burseran and Isostegane) while 2H‐HBO is an intermediate to C 7–12 5‐alk(en)yl‐γ‐lactones, which is known as Laiscent TM , a dairy flavor. LGO is a promising precursor for pharmaceuticals, with many applications having been reported in the 1980s–1990s, and with more recent examples being synthetic routes to the antiviral indinavir and a range of pharmaceutically active cyclopropylesters …”
Section: Products From C6 (Lgo and Hmf)mentioning
confidence: 99%
“…(1S,5R)-3-((E)-Benzylidene)-6,8-dioxabicyclo[3.2.1]octan-4-one (9). 2 As per the literature procedure, a mixture of benzaldehyde (2.20 g, 1.2 equiv, 20.7 mmol) and TMG (2.20 mL, 1.0 equiv, 17.2 mmol) were heated to 100 °C. Dihydrolevoglucosenone 8 (2.20 g, 1.76 mL, 1.0 equiv, 17.2 mmol) was added and the reaction mixture was stirred at 100 °C for 1 h then the mixture was directly applied to a column of silica, eluting with EtOAc/hexanes 3:17.…”
Section: S4mentioning
confidence: 99%
“…Tagirov et al reported that the acetal of Cyrene could be cleaved in ar eaction with chlorotrimethylsilane and sodium iodide to give dihydropyran-3-one derivative 3 in moderate yield (Scheme 1a). [34] In addition, they showedt hat Cyrene was a competent nucleophile for direct alkylation with benzylbromide, although ac omplexm ixture of products was obtained. [32] The Beckmann rearrangemento fC yrened erivatives can give av ariety of products depending on the specific conditions that are employed.…”
Section: Derivatization Of Cyrenementioning
confidence: 99%
“…[33] Owing to the facile enolization of Cyrene( 2)i nt he presence of as trongb ase, several groups have subjected the bicycle to aldol condensation protocols to form enones.F or example, Greatrex and co-workersreported that in the presence of tetramethylguanidine that Cyrene reactedw ith av ariety of aldehydes 10 to afford enones 11 in moderate to good yields (Scheme 3a). [34] In addition, they showedt hat Cyrene was a competent nucleophile for direct alkylation with benzylbromide, although ac omplexm ixture of products was obtained. Witczak et al reported ar elateds tudy in which they used piperidine as the base and heterocyclic aldehydes 12 in an aldol condensation reaction to afford enones 13 (Scheme 3b).…”
Section: Derivatization Of Cyrenementioning
confidence: 99%